2021
DOI: 10.1126/sciadv.abe3767
|View full text |Cite
|
Sign up to set email alerts
|

A general approach to composites containing nonmetallic fillers and liquid gallium

Abstract: We report a versatile method to make liquid metal composites by vigorously mixing gallium (Ga) with non-metallic particles of graphene oxide (G-O), graphite, diamond, and silicon carbide that display either paste or putty-like behavior depending on the volume fraction. Unlike Ga, the putty-like mixtures can be kneaded and rolled on any surface without leaving residue. By changing temperature, these materials can be stiffened, softened, and, for the G-O–containing composite, even made porous. The gallium putty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 58 publications
1
78
0
Order By: Relevance
“…However, it also led to the heat anisotropy of the composite, with a thermal conductivity of only 10.5 ± 2.3 W m −1 K −1 in the perpendicular direction. [ 12 ] Liu and his coworkers used the iron particles coated with the silver shell to mix into liquid metal and successfully extended the stability of liquid metal composite with the thermal conductivity of 48.95 ± 0.79 W m −1 K −1 . The coating process, however, is relatively complex.…”
Section: Introductionmentioning
confidence: 99%
“…However, it also led to the heat anisotropy of the composite, with a thermal conductivity of only 10.5 ± 2.3 W m −1 K −1 in the perpendicular direction. [ 12 ] Liu and his coworkers used the iron particles coated with the silver shell to mix into liquid metal and successfully extended the stability of liquid metal composite with the thermal conductivity of 48.95 ± 0.79 W m −1 K −1 . The coating process, however, is relatively complex.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the improved properties, both the density of Ga-based LMs (EGaIn: 6.25 g cm −3 ; galinstan: 6.44 g cm −3 ) and typically high loading (⩾85 wt%, or ⩾50 vol%) required to achieve the desired functional properties contribute to the high density of LM embedded composites, which can be problematic for largearea and weight-sensitive applications.Recently, researchers have shown that the properties of Gabased LMs can be enhanced through the addition of solid particles. Several LM mixtures have been studied to improve the thermo-mechanical properties [10,11,[40][41][42][43][44][45][46][47][48][49] , rheology and consistency, [50][51][52][53][54][55][56][57][58] and density [58,59] of LM. This has resulted in LM mixtures with high thermal conductivity >100 W m −1 K −1 , a fourfold increase as compared to pure LM, [43,44] LM pastes that can be easily spread on a surface, [40] and LM mixtures that can float on water.…”
mentioning
confidence: 99%
“…Recently, researchers have shown that the properties of Gabased LMs can be enhanced through the addition of solid particles. Several LM mixtures have been studied to improve the thermo-mechanical properties [10,11,[40][41][42][43][44][45][46][47][48][49] , rheology and consistency, [50][51][52][53][54][55][56][57][58] and density [58,59] of LM. This has resulted in LM mixtures with high thermal conductivity >100 W m −1 K −1 , a fourfold increase as compared to pure LM, [43,44] LM pastes that can be easily spread on a surface, [40] and LM mixtures that can float on water.…”
mentioning
confidence: 99%
“…This approach could avoid applying applied strain to make electrically conductive percolating pathways within a composite of polymeric matrices. Moreover, there are many interesting versatile properties of these new approaches that could further be explored for LM-based stretchable and wearable electronics ( de Castro et al., 2017 ; Kamysbayev et al., 2019 ; Tang et al., 2017 ; Wang et al., 2021 ; Wang et al., 2018 ).…”
Section: Biphasic Lm Alloy Conductormentioning
confidence: 99%